Konsekuensi Konflik Peran, Kelebihan Beban Kerja dan Motivasi Intrinsik terhadap Burnout pada Dosen yang Merangkap Jabatan Struktural - Eduard Yohannis Tamaela (STIE Widya Manggala, 2011)
This study has the objective to examine and analyze about the effect of relationship role conflict, work overload and intrinsic motivation toward Burnout level at lecturer who have double posts in private college. This study is an explanatory study conducted toward 6 (six) private colleges (PTS) in Ambon area using quantitative approach. Through survey by using questionnaire instrument for data collection andbased on probability sampling method also multistage cluster sampling technique for sample selection, thus the sample consists of 102 lecturers. The result of hypothesis testing through path analysis has shown that intrinsic motivation and work overload has significant effect toward Burnout while role conflict has no effect toward Burnout. Other result revealed that intrinsic motivation has been proved to have a significant effect toward role conflict.